The feasibility of using smartphone apps as treatment components for depressed suicidal outpatients - Nuij, Chani; van Ballegooijen, Wouter; de Beurs, Derek; de Winter, Remco F. P.; Gilissen, Renske; O’Connor, Rory C.; Smit, Jan H.; Kerkhof, Ad; Riper, Heleen (Frontiers in Psychiatry, 2022)
Mental health smartphone apps could increase the safety and self-management of patients at risk of suicide, but it is still unclear whether it is feasible to integrate such apps into routine mental health care. This study reports on the feasibility of using a safety planning app (BackUp) and a self-monitoring app (mEMA) as components of the routine treatment of depressed outpatients with suicidal ideation. Clinicians were trained in working with both of the apps, and they invited their eligible patients with suicidal ideation for study participation. Patients used the apps for three months and discussed these with their clinician during treatment. Patients completed assessments at baseline (T0), 4 weeks (T1) and posttest (T2, 12 weeks after baseline). Both patients and clinicians also participated in telephone interviews. Feasibility was assessed in terms of usability (score >70 on System Usability Scale, SUS), acceptability (score >20 on Client Satisfaction Questionnaire-8, CSQ-8), and uptake (sufficient rates of component completion and app usage in treatment). The sample included 17 adult outpatients (52.9% male, age range 20–50 years) diagnosed with a depressive disorder and suicidal ideation at baseline. BackUp was rated by patients at above the cut-off scores for usability (SUS mean score at T1 75.63 and at T2 77.71) and acceptability (CSQ-8 mean score at T1 23.42 and at T2 23.50). mEMA was similarly rated (SUS mean score at T1 75.83 and at T2 76.25; CSQ-8 mean score at T1 23.92 and at T2 22.75). Telephone interviews with patients and clinicians confirmed the usability and acceptability. The uptake criteria were not met. Our findings suggest that mobile safety planning and mobile self-monitoring can be considered acceptable and usable as treatment components for depressed suicidal outpatients, but the integration of apps into routine treatment needs to be further explored.